Maximization of hydropower generation through the application of a linear programming model - Yoo, Ju-Hwan (Journal of hydrology (Amsterdam), 2009)
The linear objective function is examined as an alternative to a nonlinear form with the aim of maximizing hydropower energy generation. The Yongdam multipurpose dam, located on the Geum River in South Korea, is selected as the subject of the model application. Inflow data with a reliability of 50% is applied to the model for an operation period of 12 months. This study analyzes the effect and sensitivity of the model’s release and reservoir storage on the maximization of hydropower energy generation based on calculations of optimal values. The operation according to the optimized policy is shown in terms of the given priority. The ratio between two parameters (releases and reservoir storage) is also examined in the context of the objective function of the linear model. The maximum annual energy production of the proposed model was approximately 184 GWH, which represents 86% of the potential energy production level.